The Role of Endorsers in Optimizing Sme Promotion Through Instagram Social Media in Palembang - Aquina, Salsa Melania Aquina; Zinaida, Rahma Santhi; Helmi, Sulaiman; Jabir, Bastian (Communica : Journal of Communication, 2024)
The advancement of information technology and the growing popularity of e-commerce have revolutionized marketing culture, allowing producers to connect directly with consumers through platforms like Instagram, regardless of time and location. This study, titled "The Role of Endorsers in Optimizing SME Promotion Through Instagram Social Media in Palembang," investigates how endorsers enhance SME product visibility and influence through the Instagram account @Sikonyols. By employing qualitative methods and analyzing data from the endorser’s account, followers, and collaborating SMEs, the study finds that endorsers significantly impact consumer purchasing decisions by delivering precise communication and influencing followers. This research fills a gap in understanding the effectiveness of digital marketing strategies for SMEs. The findings suggest that effective communication styles and accurate information delivery by endorsers greatly enhance promotional reach, underscoring the importance of influencer marketing in the digital era. The implications highlight that SMEs should leverage social media endorsements to optimize product promotions, significantly benefiting from reduced marketing costs and increased brand awareness.